Pengolahan Susu Sapi Menjadi Minuman Berbagai Macam Rasa - Yusroh, Mufidah; Musyarofah, Atiqatul; Fatimah, Nurul (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This training aims to process pure cow's milk into a milk drink with various flavors, namely chocolate, strawberry, and melon, through the pasteurization method. The accompanying method used in this community service is training or demonstration for students from 3rd to 5th grade at Tabita Puri Genteng Elementary School in Banyuwangi. From this traning activity, it was found that students had the skills to process cow’s milk from preparation to packaging, with sustainable impact of the P5 project implementation which is entrepeneurship and expected after knowing the process of processing until packaging, they can distribute the product on the market.